Implikatur dalam Percakapan Anak Prasekolah di Playground - Desi Afrianti; Vera Sriwahyuningsih (Journal on Education, 2023)
Implications are one of the communication strategies often used by preschoolers in playground conversations. The playground is a place where children have intense social interaction and is an ideal environment to observe how children use language and convey meaning implicitly. This research is qualitative descriptive. The techniques used in collecting data are observation techniques, fishing techniques, recording techniques, field note techniques. In the data analysis stage, researchers sort, simplify, encode, and dispose of unnecessary data. The data analysis procedure is carried out through three lines of activities that occur simultaneously to answer all formulations of this research problem, namely data reduction, data presentation and verification or conclusion. The results of data analysis found the form of conversation implications of preschoolers on the playground in the form of indirect requests, invitations to play, use of secret codes, indirect requests for help, implicit praise, plans to cooperate, invitations to share. Implications in children's conversations allow them to communicate effectively without using overly explicit words. It also helps children in developing language skills and understanding the nuances of interpersonal communication.